2018
DOI: 10.1080/19393210.2018.1484821
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of polycyclic aromatic hydrocarbons in common carp meat smoked in traditional conditions

Abstract: Common carp meat was smoked in traditional conditions without filter and with zeolite, granular activated carbon, and gravel filters. The aim of this study was to determine the influence of using different filters in traditional smoking conditions on 16 polycyclic aromatic hydrocarbons from the Environmental Protection Agency list (16 US-EPA PAHs). Determination and quantification of PAHs were performed by gas chromatography-mass spectrometry (GC-MS). According to the obtained results, all examined samples of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 28 publications
1
24
1
4
Order By: Relevance
“…Moisture content, concentration of oxygen in smoking chambers, temperature of wood combustion, etc. are also important factors for the emergence of PAHs in smoked meat products [3,4,[22][23][24][25][26]. According to different sources [1,3,8,11,[27][28][29][30][31][32], casing (natural, collagen, cellulose) acts as an obstacle and may disrupt the diffusion and deposition of smoke components into smoked foods.…”
Section: Resultsmentioning
confidence: 99%
“…Moisture content, concentration of oxygen in smoking chambers, temperature of wood combustion, etc. are also important factors for the emergence of PAHs in smoked meat products [3,4,[22][23][24][25][26]. According to different sources [1,3,8,11,[27][28][29][30][31][32], casing (natural, collagen, cellulose) acts as an obstacle and may disrupt the diffusion and deposition of smoke components into smoked foods.…”
Section: Resultsmentioning
confidence: 99%
“…Babić et al [158] evaluated the impact of zeolite, granular activated carbon, and gravel filters on PAHs levels in traditionally smoked carp meat. They observed that the smoking process using zeolite filters resulted in the lowest levels of PAHs (52.42 µg/kg).…”
Section: Reduction Of Smoke Contamination Used In the Smoking Processmentioning
confidence: 99%
“…Protein component of the food like meat are very popular in low-income communities across the world, where it is served during festivities in abundance (Zungum et al, 2020). However, many studies in recent years have shown that the second major PAHs exposure route is through consumption of food (Zhu et al, 2021;Babić et al, 2018;Duan et al, 2016;. Although, contamination of food by these pollutants is chiefly constraints on: type of fuel applied such as fuel wood, scrape tyre, liquefied petroleum gas, and kerosene.…”
Section: Occurrence Of Pahs In Foodmentioning
confidence: 99%